Capsid protein-mediated recruitment of host DnaJ-Like proteins is required for Potato Virus Y infection in tobacco plants - Sonnewald, Uwe; et al. (Journal of Virology, 2007)
The capsid protein (CP) of potyviruses is required for various steps during plant infection, such as virion assembly, cell-to-cell movement, and long-distance transport. This suggests a series of compatible interactions with putative host factors which, however, are largely unknown. By using the yeast two-hybrid system the CP from Potato virus Y (PVY) was found to interact with a novel subset of DnaJ-Iike proteins from tobacco, designated NtCPIPs. Mutational analysis identified the CP core region, previously shown to be essential for virion formation and plasmodesmal trafficking, as the interacting domain. The ability of NtCPIP1 and NtCPIP2a to associate with PVY CP could be confirmed in vitro and was additionally verified in planta by bimolecular fluorescence complementation. The biological significance of the interaction was assayed by PW infection of agroinfiltrated leaves and transgenic tobacco plants that expressed either full-length or J-domain-deficient variants of NtCPIPs. Transient expression of truncated dominant-interfering NtCPIP2a but not of the functional protein resulted in strongly reduced accumulation of PVY in the inoculated leaf. Consistently, stable overexpression of J-domain-deficient variants of NtCPIP1 and NtCPIP2a dramatically increased the virus resistance of various transgenic lines, indicating a critical role of functional NtCPIPs during PVY infection. The negative effect of impaired NtCPIP function on viral pathogenicity seemed to be the consequence of delayed cell-to-cell movement, as visualized by microprojectile bombardment with green fluorescent protein-tagged PVY. Therefore, we propose that NtCPIPs act as important susceptibility factors during PVY infection, possibly by recruiting heat shock protein 70 chaperones for viral assembly and/or cellular spread.